Experience and Truthtelling - Valverde, Mariana (Outlines. Critical Practice Studies, 2002)
This is a Foucault-inspired, postmodern study of ethical subjectivity. Technologies of life, personal truths and relations between truth telling and intoxication are highlighted in drug autobiographies and in materials from a study of Alcoholics Anonymous. Here other notions of the self are at play than the concept of the unified, autonomous, authentic self. These materials also offer an understanding of addiction as a dysfunction or disorganisation of temporality in everyday life.